Pengaruh Kompensasi Terhadap Motivasi Kerja Karyawan - Lukman Lukman; Syifa Musdhalifah Arsyad; Ihdina Sazalia Rahmah; Adliana Adliana; Adya Amalyah Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to find out whether compensation can increase work motivation in employees. This research was conducted on employees at PT. Mandala Multifinance, Tbk, Makassar 1 and Makassar 2 branches. The sample in this study was 40 respondents with the sampling technique used, namely purposive sampling. The data collection method in this research uses a Likert scale with two variables, namely motivation and compensation. The research results show that there is a significant positive influence between financial compensation and work motivation.